The Earth alignment principle for artificial intelligence - Gaffney, Owen; Luers, Amy; Carrero-Martinez, Franklin; Oztekin-Gunaydin, Berna; Creutzig, F.; Dignum, Virginia; Galaz, Victor; Ishii, N.; Larosa, F.; Leptin, Maria; Guevara, Ken Takahashi (Nature Sustainability, 2025)
At a time when the world must cut greenhouse gas emissions precipitously, artificial intelligence (AI) brings large opportunities and large risks. To address its uncertain environmental impact, we propose the ‘Earth alignment’ principle to guide AI development and deployment towards planetary stability.